CAUSES OF THE 2002-2011 IVORIAN POLITICAL ARMED CONFLICT AND IT’S RAMIFICATION ON EDUCATION - Yaro, D. S. (UDS International Journal of Development, 2019)
This study explored the causes of the 2002-2011 Ivorian political armed conflict and its ramification on education in the country. A qualitative methodology was used for the study. A purposive sampling technique was used to sample a cross section of twenty-five (25) Ivorians. A semi-structured interviewing schedule was used to gather data. The data was analysed using content analysis techniques. The study revealed that the causes of the conflict were: competing for scarce resources, incessant political power struggles, land claims, problematic electoral processes, unemployment, discrimination among the ethnic groups, and succession problems with political transition. The ramifications of the conflict for education were: destruction of school infrastructure, the closure of schools in the North, decrease of the student population, and fleeing of teachers for fear of insecurity. Based on the findings, the following recommendations were proffered: the Government should assure teachers of peace and encourage them by increasing their salaries to enable them to return to the country. Traumatised educational workers and students should be counselled and the calendar of the school should be kept in order to assist the students catch up with their lost time as well as to promote pro-democratic practices and beliefs in schools. Keywords: ECOWAS, Ivory Coast, Ramification, Education, Armed conflict